Feasibility Study of Maize Cobs as Throatless Gasifier Feedstock - Chopra, Sangeeta; Jain, A K; Dhingra, Devinder (Journal of Agricultural Engineering, 2013)
Fuel properties of maize cob and its gasification feasibility in throatless downdraft gasifier were investigated.Performance of the throatless gasifier using producer gas from maize cobs was evaluated in terms of fuel consumptionrate, heating value of producer gas and gasification efficiency at different gas flow rates. Gasification efficiencyincreased with increasing gas flow rate, and was maximum (67.37 %) at specific gasification rate (SGR) of 169.95kg.h-1.m-2 and gas flow of 33.02 Nm3.h-1. Further increase in gas flow rate reduced gasification efficiency. Energybalance for the run had maximum efficiency. Each unit of energy input to the gasifier in the form of maize cobs wasconverted to 67.18 % chemical energy of producer gas and 16.82 % char residue, respectively. Sensible energy ofgas and char residue was 6.51 % and 0.11 %, respectively. The unaccounted losses were 9.38 per cent. Maize cobscould thus be successfully used as feedstock for throatless gasifier.